CONTEMPT OF COURT DI INDONESIA, PERLUKAH? - Otto Hasibuan (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2015)
Contempt of Court law needs to be made apart with specific law, but waiting or at least fulfillment at once the changed of law system with the comprehendship way and improving the professionalism of judge, attorney, police officer, advocat, journalist, and socialization to the society of justice seeker.Keywords : Contempt of Court, Indonesia